Study on Companies from the Energy Sector from the Perspective of Performance through the Operating Cash Flow - Claudia Diana Sabău-Popa; Luminița Rus; Dana Simona Gherai; Codruța Mare; Ioan Gheorghe Țara (Energies, 2021)
In this paper we analyzed the link between companies’ performance, in terms of cash and income, and the labor productivity or management rates, in case of the companies from the energy sector listed on the Bucharest Stock Exchange. We focused on the energy sector because of the impact that its expansion has on the evolution of economies around the world and because of its dynamics in the sense of gradually shifting to the use of energy from renewable sources. We have used panel regression models to analyze the operating cash flow and the profitability rates and the determination of a causal or dependency relationship with labor productivity or management rates. The results of this study show a significant negative correlation between operating cash flows and the average duration of stock rotation, and no correlation between productivity and the operating cash flow. Instead, the average duration of stock turnover does not at all influence the profitability rates, and productivity is always significant for the return on assets, ie forthe return on equitywith a positive coefficient, as expected. The gap between the average duration of payment of suppliers and the average duration of receivables does not significantly influence neither the cash flow nor the rates of return.